Amphiphilic polymers, methods of making and using the same
By preparing amphoteric polymers with high charge density and a network structure, the problems of poor temperature resistance and compatibility of existing clay stabilizers in high-temperature and ultra-high-temperature reservoir stimulation have been solved. This has achieved efficient clay control and water washing resistance, making it suitable for fracturing stimulation of high-temperature and ultra-high-temperature reservoirs.
Patent Information
- Application Number
- CN202511763590.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-27
- Publication Date
- 2026-02-10
- Estimated Expiration
- 2045-11-27
AI Technical Summary
Existing polymer clay stabilizers have poor temperature resistance, salt resistance, and compatibility in high-temperature and ultra-high-temperature reservoir stimulation, and cannot meet the stimulation requirements of high-temperature and ultra-high-temperature reservoirs.
An amphoteric polymer was prepared by copolymerizing anionic monomers, a first cationic monomer, a second cationic monomer, and a crosslinking monomer. Combined with a chain transfer agent and an initiator, the polymer was formed with high charge density, a network structure, and multiple hydrophobic short chains, exhibiting good temperature resistance and compatibility with fracturing fluids.
It effectively inhibits clay hydration and expansion under high and ultra-high temperature conditions, has a high anti-swelling rate, excellent water washing resistance, and does not impair the sand-carrying capacity of fracturing fluid, making it suitable for fracturing stimulation of high and ultra-high temperature reservoirs.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of oilfield chemical technology, specifically to an amphoteric polymer, its preparation method, and its applications. Background Technology
[0002] During water injection and acid fracturing in oilfields, clay minerals (such as kaolinite, montmorillonite, illite, and chlorite) in the formation expand, disperse, and migrate when they encounter external water or water-based substances. This can even clog pore channels, reducing formation permeability and severely damaging low-permeability reservoirs. Adding clay stabilizers to the well fluid can prevent clay hydration, expansion, dispersion, and migration, thus protecting the reservoir. Clay particles typically carry a negative charge, while the cations in the clay stabilizer are positively charged. Through electrostatic attraction, they generate a strong adsorption effect, slowing down water molecule penetration and preventing the hydration and expansion of clay minerals, thereby inhibiting water hydration.
[0003] With the development of oil fields, the application of clay stabilizers has become more and more widespread and diverse. Based on different structures and the different chemicals used, they can be roughly divided into three stages: from the 1950s to the late 1960s, inorganic salt clay stabilizers were mainly used; in the 1970s, inorganic polynuclear polymers and cationic surfactant clay stabilizers were mainly used; and after the 1980s, the use of cationic organic polymer clay stabilizers was mainly developed.
[0004] Inorganic salt clay stabilizers are inexpensive but require large quantities, are not resistant to water washing, have a short shelf life, and can negatively impact the performance of injection fluids. Inorganic polynuclear polymer clay stabilizers suffer from poor temperature and acid resistance. Cationic surfactant clay stabilizers can alter reservoir wettability and reduce recovery rates. Polyquaternary ammonium and other polymeric swelling inhibitors have poor thermal stability. Furthermore, with the development of low-to-medium permeability reservoirs, polymeric polymeric swelling inhibitors, due to their large molecular weight, can easily damage the reservoir, leading to reduced permeability and increased difficulty in water injection. In addition, the aforementioned cationic clay stabilizers have poor compatibility with fracturing fluids, significantly reducing the proppant-carrying capacity of the fracturing fluid and increasing the difficulty of proppant addition during fracturing operations. Simultaneously, in high-temperature and ultra-high-temperature reservoir environments, conventional clay stabilizers lose stability due to excessively high temperatures and cannot effectively inhibit clay hydration and swelling.
[0005] Chinese patent document CN104098738A discloses a method for preparing a low molecular weight polymer clay stabilizer. This low molecular weight polymer clay stabilizer is prepared by copolymerization in an aqueous solution using ammonium salts containing carbon-carbon double bonds and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) as raw materials. The polymer's number-average molecular weight is less than 50,000. The introduction of sulfonic acid groups increases the polymer's water solubility and temperature resistance; in water, it can simultaneously form multi-point adsorption with multiple clay particles, and after adsorption, an adsorption protective film is formed on the surface of the clay particles, preventing their expansion and migration; the temperature resistance reaches 120℃. However, the temperature resistance of this clay stabilizer is still insufficient for high-temperature and ultra-high-temperature reservoir stimulation.
[0006] Chinese patent document CN119119987A discloses a high-temperature resistant anti-swelling agent for heavy oil in offshore oilfields and its preparation method. This high-temperature resistant anti-swelling agent comprises the following components by mass percentage: 15-25% small-molecule cationic functional agent, 10-15% high-molecule cationic functional agent, 1.0-1.5% surface modifier, 10-15% additives, and the balance being water. This high-temperature resistant anti-swelling agent can withstand operating environments up to 300℃, tolerate reservoir produced water with a total salinity of less than or equal to 20,000 mg / L, and does not damage the formation, thus protecting the environment. Using a 4% concentration of the high-temperature anti-swelling agent working solution, after aging at 300℃ for 24 hours, the anti-swelling rate exceeds 90%, and the water wash resistance rate exceeds 90%. However, small molecule cationic functional agents, high molecule cationic functional agents, and surface modifiers are all cationic, and the additives are inorganic salts. Therefore, this temperature-resistant anti-swelling agent has poor compatibility with fracturing fluids and does not meet the requirements of reservoir stimulation operations such as hydraulic fracturing and acidizing.
[0007] Therefore, developing low molecular weight amphoteric polymer clay stabilizers to meet the needs of high-temperature and ultra-high-temperature reservoir stimulation has significant practical implications. Summary of the Invention
[0008] This invention provides an amphoteric polymer and its preparation method, overcoming the shortcomings of the prior art. It can effectively solve the problems of poor temperature resistance, salt resistance, and compatibility of existing polymer clay stabilizers, thus meeting the needs of high-temperature and ultra-high-temperature reservoir transformation.
[0009] One of the technical solutions of the present invention is achieved through the following measures: an amphoteric polymer, obtained by copolymerization of anionic monomer, a first cationic monomer, a second cationic monomer and a crosslinking monomer;
[0010] The anionic monomer is one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methpropylene sulfonate, sodium p-styrene sulfonate, sodium (4-vinyl)phenylmethanesulfonate, sodium 3-allyloxy-2-hydroxy-1-propane sulfonate, or sodium 2-acrylamido-2-methylpropanesulfonate.
[0011] The first cationic monomer is N-allyl-N,N-dimethylcyclohexylammonium chloride;
[0012] The second cationic monomer is allyltributylphosphine chloride;
[0013] The crosslinking monomer is N,N'-methylenebisacrylamide.
[0014] The following are further optimizations and / or improvements to one of the above-mentioned technical solutions:
[0015] The mass ratio of the above-mentioned anionic monomer, first cationic monomer, second cationic monomer and crosslinking monomer is 5 to 20: 50 to 80: 5 to 25: 0.01 to 0.1.
[0016] The chemical structural formulas of the above amphoteric polymers are as follows:
[0017]
[0018] In the formula, M1 is the structural unit of the anionic monomer, and m1 to m4 are the number of each structural unit.
[0019] The first cationic monomer, N-allyl-N,N-dimethylcyclohexylammonium chloride, was prepared according to the following steps:
[0020] N,N-dimethylcyclohexylamine and allyl chloride were dissolved in a reaction solvent, and after the reaction, N-allyl-N,N-dimethylcyclohexylammonium chloride was obtained.
[0021] The reaction temperature is between 25℃ and 50℃, and the reaction time is between 6h and 12h.
[0022] Or / and; the molar ratio of N,N-dimethylcyclohexylamine to allyl chloride is 1 to 1.5:1;
[0023] Or / and; the reaction solvent is acetonitrile or ethyl acetate.
[0024] The above-mentioned second cationic monomer, allyltributylphosphine chloride, is prepared according to the following steps:
[0025] Tributylphosphine and allyl chloride were added to a solvent and refluxed. The product was concentrated, recrystallized and dried to obtain allyltributylphosphine chloride.
[0026] The reflux reaction temperature is 80℃ to 85℃, and the reflux reaction time is 12h to 36h.
[0027] Or / and; the molar ratio of tributylphosphine to allyl chloride is 1:1 to 1.5;
[0028] Or / and; the solvent is acetonitrile or ethanol.
[0029] The above-mentioned amphoteric polymer was prepared according to the following steps:
[0030] Step 1: Add anionic monomer, first cationic monomer, second cationic monomer, crosslinking monomer and chain transfer agent to water to obtain a reaction mixture;
[0031] Step two: Add an initiator to the reaction mixture. After the reaction, an amphoteric polymer is obtained.
[0032] In the above reaction mixture, the total mass percentage of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer is 25 wt% to 75 wt%.
[0033] The chain transfer agent mentioned above is one or more of sodium formate, 2-mercaptoethanol, and mercaptoacetic acid, and the amount of chain transfer agent used is 0.1% to 2% of the total mass of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer.
[0034] The reaction temperature is 40℃ to 70℃, and the reaction time is 4h to 12h.
[0035] In step two above, the initiator is added after the dissolved oxygen in the reaction mixture is removed.
[0036] The second technical solution of the present invention is achieved through the following measures: a method for preparing an amphoteric polymer, comprising the following steps:
[0037] Step 1: Add anionic monomer, first cationic monomer, second cationic monomer, crosslinking monomer and chain transfer agent to water to obtain a reaction mixture;
[0038] Step two: Add an initiator to the reaction mixture. After the reaction, an amphoteric polymer is obtained.
[0039] The third technical solution of the present invention is achieved through the following measures: the application of an amphoteric polymer in clay stabilizers.
[0040] This invention provides an amphoteric polymer, its preparation method, and its applications. This amphoteric polymer exhibits high charge density, demonstrating outstanding performance as a clay stabilizer with high anti-swelling rate. It possesses abundant adsorption sites and strong adsorption capacity, along with a network structure and multiple hydrophobic short chains, resulting in excellent water washability. Furthermore, the polymer structure includes a cross-linked network, a cyclic structure, and sulfonic acid groups, endowing it with good temperature resistance, making it suitable for high-temperature and even ultra-high-temperature reservoir conditions. In addition, the anionic structural units introduced into the polymer reduce its impact on fracturing fluid performance and do not impair the fracturing fluid's proppant-carrying capacity. The preparation method of this amphoteric polymer is simple, and the reaction process is safe and controllable, facilitating large-scale production and widespread application. Detailed Implementation
[0041] This invention is not limited to the following embodiments, and specific implementation methods can be determined according to the technical solution of this invention and the actual situation. Unless otherwise specified, all chemical reagents and chemical products mentioned in this invention are well-known and commonly used chemical reagents and chemical products in the prior art; unless otherwise specified, all percentages in this invention are mass percentages; room temperature in this invention generally refers to a temperature between 15°C and 25°C, and is generally defined as 25°C.
[0042] The present invention will be further described below with reference to embodiments:
[0043] Example 1: This amphoteric polymer is obtained by copolymerization of anionic monomers, a first cationic monomer, a second cationic monomer, and a crosslinking monomer;
[0044] The anionic monomer is one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methpropylene sulfonate, sodium p-styrene sulfonate, sodium (4-vinyl)phenylmethanesulfonate, sodium 3-allyloxy-2-hydroxy-1-propane sulfonate, or sodium 2-acrylamido-2-methylpropanesulfonate.
[0045] The first cationic monomer is N-allyl-N,N-dimethylcyclohexylammonium chloride;
[0046] The second cationic monomer is allyltributylphosphine chloride;
[0047] The crosslinking monomer is N,N'-methylenebisacrylamide.
[0048] The chemical structural formula of N-allyl-N,N-dimethylcyclohexylammonium chloride is as follows:
[0049] .
[0050] The chemical structural formula of allyltributylphosphine chloride is as follows:
[0051] .
[0052] Example 2: As an optimization of the above example, the mass ratio of the anionic monomer, the first cationic monomer, the second cationic monomer and the crosslinking monomer is 5 to 20: 50 to 80: 5 to 25: 0.01 to 0.1.
[0053] Example 3: As an optimization of the above examples, the chemical structure of the amphoteric polymer is as follows:
[0054]
[0055] In the formula, M1 is the structural unit of the anionic monomer; m1 to m4 are the number of structural units, respectively.
[0056] Example 4: As an optimization of the above examples, the first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride was prepared according to the following steps:
[0057] N,N-dimethylcyclohexylamine and allyl chloride were dissolved in a reaction solvent, and after the reaction, N-allyl-N,N-dimethylcyclohexylammonium chloride was obtained; the reaction mechanism is as follows:
[0058] .
[0059] Example 5: As an optimization of Example 4 above, the reaction temperature is 25°C to 50°C, and the reaction time is 6h to 12h;
[0060] Or / and; the molar ratio of N,N-dimethylcyclohexylamine to allyl chloride is 1 to 1.5:1;
[0061] Or / and; the reaction solvent is acetonitrile or ethyl acetate.
[0062] Example 6: As an optimization of the above examples, the second cationic monomer allyltributylphosphine chloride was prepared according to the following steps:
[0063] Tributylphosphine and allyl chloride were added to a solvent and refluxed. The product was concentrated, recrystallized, and dried to obtain allyltributylphosphine chloride. The reaction mechanism is as follows:
[0064] .
[0065] Example 7: As an optimization of Example 6 above, the reflux reaction temperature is 80°C to 85°C, and the reflux reaction time is 12h to 36h;
[0066] Or / and; the molar ratio of tributylphosphine to allyl chloride is 1:1 to 1.5;
[0067] Or / and; the solvent is acetonitrile or ethanol.
[0068] Example 8: As an optimization of the above examples, the amphoteric polymer was prepared according to the following steps:
[0069] Step 1: Add anionic monomer, first cationic monomer, second cationic monomer, crosslinking monomer and chain transfer agent to water to obtain a reaction mixture;
[0070] Step two: Add an initiator to the reaction mixture. After the reaction, an amphoteric polymer is obtained.
[0071] Example 9: As an optimization of Example 8 above, the total mass percentage of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer in the reaction mixture is 25 wt% to 75 wt%.
[0072] Example 10: As an optimization of Example 8 above, the chain transfer agent is one or more of sodium formate, 2-mercaptoethanol, and mercaptoacetic acid, and the amount of chain transfer agent is 0.1% to 2% of the total mass of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer.
[0073] Example 11: As an optimization of Example 8 above, the reaction temperature is 40°C to 70°C and the reaction time is 4h to 12h.
[0074] Example 12: As an optimization of Example 8 above, in step two, an initiator is added after the dissolved oxygen in the reaction mixture is removed.
[0075] Example 13: Application of this amphoteric polymer in clay stabilizers.
[0076] Example 14: Preparation of N-allyl-N,N-dimethylcyclohexylammonium chloride:
[0077] 0.12 mol of N,N-dimethylcyclohexylamine and 0.1 mol of allyl chloride were dissolved in 100 mL of acetonitrile and reacted at 25 °C for 12 h. The reaction product was frozen, filtered, washed with ethyl acetate, and dried under vacuum to obtain a white solid N-allyl-N,N-dimethylcyclohexylammonium chloride.
[0078] In this embodiment, the yield of N-allyl-N,N-dimethylcyclohexylammonium chloride was 96.4%.
[0079] Example 15: Preparation of N-allyl-N,N-dimethylcyclohexylammonium chloride:
[0080] 0.12 mol of N,N-dimethylcyclohexylamine and 0.1 mol of allyl chloride were dissolved in 100 mL of acetonitrile and reacted at 50 °C for 8 h. The reaction product was frozen, filtered, washed with ethyl acetate, and dried under vacuum to obtain a white solid N-allyl-N,N-dimethylcyclohexylammonium chloride.
[0081] In this embodiment, the yield of N-allyl-N,N-dimethylcyclohexylammonium chloride was 99.7%.
[0082] Example 16: Preparation of N-allyl-N,N-dimethylcyclohexylammonium chloride:
[0083] 0.15 mol of N,N-dimethylcyclohexylamine and 0.1 mol of allyl chloride were dissolved in 100 mL of ethyl acetate and reacted at 50 °C for 6 h. The reaction product was frozen, filtered, washed with ethyl acetate, and dried under vacuum to obtain a white solid N-allyl-N,N-dimethylcyclohexylammonium chloride.
[0084] In this embodiment, the yield of N-allyl-N,N-dimethylcyclohexylammonium chloride was 99.6%.
[0085] Example 17: Preparation of allyltributylphosphine chloride:
[0086] 0.1 mol of tributylphosphine and 0.1 mol of allyl chloride were dissolved in 100 mL of acetonitrile and refluxed at 80 °C for 36 h. The reaction product was then subjected to rotary evaporation, recrystallization with ethyl acetate, and vacuum drying to obtain a white solid allyltributylphosphine chloride.
[0087] In this embodiment, the yield of allyltributylphosphine chloride was 88.1%.
[0088] Example 18: Preparation of allyltributylphosphine chloride:
[0089] 0.1 mol of tributylphosphine and 0.12 mol of allyl chloride were dissolved in 100 mL of acetonitrile and refluxed at 85 °C for 24 h. The reaction product was then subjected to rotary evaporation, recrystallization with ethyl acetate, and vacuum drying to obtain a white solid allyltributylphosphine chloride.
[0090] In this example, the yield of allyltributylphosphine chloride was 99.5%.
[0091] Example 19: Preparation of allyltributylphosphine chloride:
[0092] 0.1 mol of tributylphosphine and 0.15 mol of allyl chloride were dissolved in 100 mL of anhydrous ethanol and refluxed at 85 °C for 24 h. The reaction product was subjected to rotary evaporation, recrystallization with ethyl acetate, and vacuum drying to obtain a white solid allyltributylphosphine chloride.
[0093] In this embodiment, the yield of allyltributylphosphine chloride was 99.8%.
[0094] Example 20: Preparation of amphoteric polymers:
[0095] In this example, N-allyl-N,N-dimethylcyclohexylammonium chloride was prepared in Example 14, and allyltributylphosphine chloride was prepared in Example 17.
[0096] 2.5g of anionic monomer sodium vinyl sulfonate, 20.0g of the first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 2.5g of the second cationic monomer allyltributylphosphine chloride, 0.025g of crosslinking monomer N,N'-methylenebisacrylamide, and 0.05g of chain transfer agent sodium formate were added to 75.0g of tap water to obtain a reaction mixture.
[0097] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.25 g of ammonium persulfate initiator was added, stirred until homogeneous, and the mixture was heated to 40 °C and reacted for 12 hours to obtain an amphoteric polymer, denoted as S1.
[0098] Example 21: Preparation of amphoteric polymers:
[0099] In this example, N-allyl-N,N-dimethylcyclohexylammonium chloride was prepared in Example 14, and allyltributylphosphine chloride was prepared in Example 17.
[0100] 7.5g of anionic monomer sodium allyl sulfonate, 35.0g of the first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 7.5g of the second cationic monomer allyl tributylphosphine chloride, 0.025g of crosslinking monomer N,N'-methylenebisacrylamide, and 0.1g of chain transfer agent 2-mercaptoethanol were added to 50.0g of tap water to obtain a reaction mixture.
[0101] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.25 g of potassium persulfate initiator was added, and the mixture was heated to 40 °C and reacted for 6 hours to obtain an amphoteric polymer, denoted as S2.
[0102] Example 22: Preparation of amphoteric polymers:
[0103] In this example, N-allyl-N,N-dimethylcyclohexylammonium chloride was prepared in Example 15, and allyltributylphosphine chloride was prepared in Example 18.
[0104] 12.0 g of anionic monomer 3-allyloxy-2-hydroxy-1-propanesulfonate sodium, 36.0 g of first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 12.0 g of second cationic monomer allyltributylphosphine chloride, 0.03 g of crosslinking monomer N,N'-methylenebisacrylamide, and 0.06 g of chain transfer agent mercaptoacetic acid were added to 40.0 g of tap water to obtain a reaction mixture.
[0105] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.4 g of initiator azobisisobutylamidine hydrochloride was added, and the mixture was heated to 70 °C and reacted for 4 hours to obtain an amphoteric polymer, denoted as S3.
[0106] Example 23: Preparation of amphoteric polymers:
[0107] In this example, N-allyl-N,N-dimethylcyclohexylammonium chloride was prepared in Example 16, and allyltributylphosphine chloride was prepared in Example 19.
[0108] 10.0g of anionic monomer sodium allyl sulfonate, 2.5g of anionic monomer sodium p-styrene sulfonate, 50.0g of the first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 12.5g of the second cationic monomer allyl tributylphosphine chloride, 0.03g of crosslinking monomer N,N'-methylenebisacrylamide, and 0.75g of chain transfer agent sodium formate were added to 25.0g of tap water to obtain a reaction mixture.
[0109] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.5 g of ammonium persulfate and 0.25 g of azobisisobutylamidine hydrochloride were added, and the mixture was heated to 50 °C and reacted for 6 hours to obtain an amphoteric polymer, denoted as S4.
[0110] Comparative Example 1: No anionic monomer sodium allyl sulfonate was added in this comparative example.
[0111] 22.5g of the first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 2.5g of the second cationic monomer allyltributylphosphine chloride, 0.025g of the crosslinking monomer N,N'-methylenebisacrylamide, and 0.05g of the chain transfer agent sodium formate were added to 75.0g of tap water to obtain a reaction mixture.
[0112] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.25 g of ammonium persulfate initiator was added, stirred until homogeneous, and the mixture was heated to 40 °C and reacted for 12 hours to obtain an amphoteric polymer, denoted as D1.
[0113] Comparative Example 2: No first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride was added in this comparative example.
[0114] 7.5g of anionic monomer sodium allyl sulfonate, 42.5g of second cationic monomer allyl tributylphosphine chloride, 0.025g of crosslinking monomer N,N'-methylenebisacrylamide and 0.1g of chain transfer agent 2-mercaptoethanol were added to 50.0g of tap water to obtain a reaction mixture.
[0115] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.25 g of potassium persulfate initiator was added, and the mixture was heated to 40 °C and reacted for 6 hours to obtain an amphoteric polymer, denoted as D2.
[0116] Comparative Example 3: No second cationic monomer, allyltributylphosphine chloride, was added in this comparative example.
[0117] 12.0 g of anionic monomer 3-allyloxy-2-hydroxy-1-propanesulfonate sodium, 48.0 g of first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 0.03 g of crosslinking monomer N,N'-methylenebisacrylamide, and 0.06 g of chain transfer agent mercaptoacetic acid were added to 40.0 g of tap water to obtain a reaction mixture.
[0118] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.4 g of initiator azobisisobutylamidine hydrochloride was added, and the mixture was heated to 70 °C and reacted for 4 hours to obtain an amphoteric polymer, denoted as D1.
[0119] Comparative Example 4: No cross-linking monomer N,N'-methylenebisacrylamide was added in this comparative example.
[0120] 10.0g of anionic monomer sodium allyl sulfonate, 2.5g of anionic monomer sodium p-styrene sulfonate, 50.0g of the first cationic monomer N-allyl-N,N-dimethylcyclohexylammonium chloride, 12.5g of the second cationic monomer allyl tributylphosphine chloride, and 0.75g of chain transfer agent sodium formate were added to 25.0g of tap water to obtain a reaction mixture.
[0121] Nitrogen gas was bubbled through the reaction mixture for 15 minutes to remove dissolved oxygen. Then, 0.5 g of ammonium persulfate and 0.25 g of azobisisobutylamidine hydrochloride were added, and the mixture was heated to 50 °C and reacted for 6 hours to obtain an amphoteric polymer, denoted as D4.
[0122] Performance testing:
[0123] Test Example 1: Evaluation of the anti-swelling rate of amphoteric polymers as clay stabilizers
[0124] Take a certain amount of amphoteric polymers S1 to S4 and D1 to D4, add them to 100g of distilled water respectively, and shake well to obtain clay stabilizer solutions with the designed test concentrations (see Table 1). Weigh 0.50g of sodium bentonite, put it into a 10mL centrifuge tube, add 10mL of clay stabilizer solution, shake well, let it stand at room temperature for 2h, put it into a centrifuge, and centrifuge at 1500r / min for 15min. Read the volume V1 of the expanded sodium bentonite.
[0125] The volume V2 of sodium bentonite after expansion is calculated by replacing the clay stabilizer solution with distilled water.
[0126] When kerosene is used instead of clay stabilizer solution, the volume V0 of sodium bentonite after expansion is calculated.
[0127] Calculate the anti-expansion rate using the following formula: .
[0128] The test results of the anti-swelling rate of amphoteric polymers S1 to S4 and D1 to D4 as clay stabilizers are shown in Table 1.
[0129] Test Example 2: Evaluation of the water wash resistance of amphoteric polymers as clay stabilizers:
[0130] Discard the supernatant in the centrifuge tube after centrifugation in Test Example 1, add 10 mL of distilled water, shake well, let stand for 2 hours, put it into a centrifuge, centrifuge at 1500 r / min for 15 min, repeat the above operation twice, read the volume of sodium bentonite after expansion, and calculate the anti-swelling rate in the same way as in Test Example 1.
[0131] The test results of the water washability of amphoteric polymers S1 to S4 and D1 to D4 as clay stabilizers are shown in Table 1.
[0132] Test Example 3: Evaluation of viscosity retention rate of polymer fracturing fluid using amphoteric polymers as clay stabilizers:
[0133] Prepare 1000 mL of 0.2% polymer fracturing fluid (Chengdu Lauenpus Technology Co., Ltd.) base solution, divide it into two equal parts, add an amphoteric polymer to the other part to obtain a clay stabilizer solution (concentration same as in Test Example 1), and use one part as a blank sample. Stir for 5 min. Let both samples stand at room temperature for 2 h, and test the apparent viscosity of the blank sample and the sample after adding the amphoteric polymer.
[0134] Calculate viscosity retention using the following formula:
[0135]
[0136] In the formula, y1 is the viscosity retention rate, expressed as a percentage; η2 is the apparent viscosity of the sample with clay stabilizer added, in mPa·s; and η1 is the apparent viscosity of the blank sample, in mPa·s.
[0137] The viscosity retention test results of amphoteric polymers S1 to S4 and D1 to D4 are shown in Table 1.
[0138] The clay stabilizer solution was placed in a high-temperature and high-pressure heat treatment sealed container and heat-treated at 300°C for 2 hours. The above operation was repeated to test the temperature resistance of the clay stabilizer. The test results are shown in Table 1.
[0139] Table 1
[0140] .
[0141] As can be seen from the test results in Table 1, the amphoteric polymer of the present invention, as a clay stabilizer, exhibits an anti-swelling rate of ≥90% at room temperature and 300℃, an anti-swelling rate of ≥89% after water washing, and a viscosity retention rate of ≥85% for polymer fracturing fluid. It also has a temperature resistance up to 300℃, demonstrating excellent performance and is suitable for fracturing and stimulation of high-temperature, ultra-high-temperature, and ultra-low-permeability reservoirs.
[0142] In summary, this invention provides an amphoteric polymer and its preparation method. This amphoteric polymer exhibits high charge density, numerous adsorption sites, and strong adsorption capacity. Structurally, it possesses a network structure, multiple hydrophobic short chains, a cross-linked network, a cyclic structure, and sulfonic acid groups. As a clay stabilizer, it demonstrates high efficiency, high anti-swelling rate, and strong resistance to water washing and high temperatures, making it suitable for fracturing in high-temperature and ultra-high-temperature reservoirs. Furthermore, the preparation method for this amphoteric polymer is simple, and the reaction process is safe and controllable, facilitating large-scale production and widespread application.
[0143] The above technical features constitute various embodiments of the present invention, which have strong adaptability and implementation effect. Unnecessary technical features can be added or removed according to actual needs to meet the needs of different situations.
Claims
1. An amphoteric polymer, characterized in that... It is obtained by copolymerization of anionic monomer, first cationic monomer, second cationic monomer and crosslinking monomer; The anionic monomer is one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methpropylene sulfonate, sodium p-styrene sulfonate, sodium (4-vinyl)phenylmethanesulfonate, sodium 3-allyloxy-2-hydroxy-1-propane sulfonate, or sodium 2-acrylamido-2-methylpropanesulfonate. The first cationic monomer is N-allyl-N,N-dimethylcyclohexylammonium chloride; The second cationic monomer is allyltributylphosphine chloride; The crosslinking monomer is N,N'-methylenebisacrylamide; The mass ratio of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer is 5 to 20: 50 to 80: 5 to 25: 0.01 to 0.
1.
2. The amphoteric polymer according to claim 1, characterized in that... The chemical structural formula is as follows: In the formula, M1 is the structural unit of the anionic monomer, and m1 to m4 are the number of each structural unit.
3. The amphoteric polymer according to claim 1, characterized in that... The first cationic monomer, N-allyl-N,N-dimethylcyclohexylammonium chloride, was prepared according to the following steps: N,N-dimethylcyclohexylamine and allyl chloride were dissolved in a reaction solvent, and after the reaction, N-allyl-N,N-dimethylcyclohexylammonium chloride was obtained.
4. The amphoteric polymer according to claim 3, characterized in that... The reaction temperature is 25℃ to 50℃, and the reaction time is 6h to 12h; Or / and, the molar ratio of N,N-dimethylcyclohexylamine to allyl chloride is 1 to 1.5:1; Or / and, the reaction solvent is acetonitrile or ethyl acetate.
5. The amphoteric polymer according to claim 1, characterized in that... The second cationic monomer, allyltributylphosphine chloride, was prepared according to the following steps: Tributylphosphine and allyl chloride were added to a solvent and refluxed. The product was concentrated, recrystallized and dried to obtain allyltributylphosphine chloride.
6. The amphoteric polymer according to claim 5, characterized in that... The reflux reaction temperature is 80℃ to 85℃, and the reflux reaction time is 12h to 36h; Or / and, the molar ratio of tributylphosphine to allyl chloride is 1:1 to 1.5; Or / and, the solvent is acetonitrile or ethanol.
7. The amphoteric polymer according to claim 1, characterized in that... The amphoteric polymer was prepared according to the following steps: Step 1: Add anionic monomer, first cationic monomer, second cationic monomer, crosslinking monomer and chain transfer agent to water to obtain a reaction mixture; Step two: Add an initiator to the reaction mixture. After the reaction, an amphoteric polymer is obtained.
8. The amphoteric polymer according to claim 7, characterized in that... In the reaction mixture, the total mass percentage of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer is 25 wt% to 75 wt%.
9. The amphoteric polymer according to claim 7 or 8, characterized in that... The chain transfer agent is one or more of sodium formate, 2-mercaptoethanol, and mercaptoacetic acid, and the amount of chain transfer agent used is 0.1% to 2% of the total mass of the anionic monomer, the first cationic monomer, the second cationic monomer, and the crosslinking monomer.
10. The amphoteric polymer according to claim 7, characterized in that... In step two, the reaction temperature is 40℃ to 70℃, and the reaction time is 4h to 12h.
11. The amphoteric polymer according to claim 7 or 8, characterized in that... In step two, the initiator is added after the dissolved oxygen in the reaction mixture is removed.
12. A method for preparing an amphoteric polymer according to any one of claims 1 to 11, characterized in that... Follow these steps: Step 1: Add anionic monomer, first cationic monomer, second cationic monomer, crosslinking monomer and chain transfer agent to water to obtain a reaction mixture; Step two: Add an initiator to the reaction mixture. After the reaction, an amphoteric polymer is obtained.
13. The use of an amphoteric polymer according to any one of claims 1 to 11 in the field of clay stabilizers.
Citation Information
Patent Citations
Preparation method of low molecular weight clay stabilizer
CN104098738A
Temperature-resistant anti-swelling agent for thermal recovery of offshore oilfield thickened oil and preparation method of temperature-resistant anti-swelling agent
CN119119987A
High-temperature-resistant polymer thickening agent for oil field fracturing fluid as well as preparation method and application of thickening agent
CN104449643A
Demulsifier for eliminating oil-water interface emulsion layer in oilfield produced liquid treatment and preparation method thereof
CN119978225A